The Psychological Characteristics of the Children of Israel in the Qur'an: A Thematic Analysis of Verses Describing the Children of Israel According to Sayyid Qutb - Wanda Alifi Wirawan; Mohammad Zakki Azani; Mahasri Shobahiya (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to examine the psychological characteristics of the Children of Israel as described in the Qur'an through an analysis of Sayyid Qutb's Fi Zilal al-Qur'an, with a focus on collective behavior patterns and historical factors that shaped their characteristics, such as rebelliousness, materialistic tendencies, racial arrogance, inconsistency in faith, and dependence on worldly power. This study uses a qualitative method with a library research approach, combining thematic analysis of Qur'anic verses and a psychological-historical approach to understand their psychological dynamics in the context of oppression and liberation. The results of the study show that, according to Sayyid Qutb, the character of the Children of Israel was the result of collective trauma caused by slavery in Egypt, which gave rise to spiritual inferiority, defiance of God's commands, and a materialistic orientation that shifted divine values. racial and intellectual arrogance reflects a deviation in understanding the concept of the “chosen people,” while inconsistency in faith represents spiritual hypocrisy that weakens monotheism. Qutb viewed this pattern as a universal phenomenon that serves as a warning to all of humanity not to get caught up in formal religious practices without spiritual depth. The main value of this research lies in its contribution to enriching thematic interpretation studies through a psychological-historical approach, emphasizing the relationship between human inner conditions and historical experiences in the formation of religious character, and encouraging Muslims to cultivate authentic, humble faith oriented towards the mandate of revelation, rather than outward symbols or claims of group superiority.